AN ANALYSIS OF OUTPATIENT HEALTHCARE SERVICE QUALITY USING IMPORTANCE PERFORMANCE ANALYSIS (IPA) AND THE KANO MODEL - Febi Alfina (J@ti Undip: Jurnal Teknik Industri, 2026)
Healthcare service play a vital role in maintaining, restoring, and improving individual and community health, particularly through primary healthcare facilities such as puskesmass. As frontline healthcare providers, puskesmas are required to deliver high quality services to ensure patient satisfaction and trust. However, Puskesmas Ulee Kareng in Banda Aceh City faces challenges in service quality, as indicated by patient complaints regarding waiting times of 15-20 minutes following the implementation of an online registration system. These delays are caused by limited patient understanding of online form completion and inadequate internet access. This study aims to measure patient satisfaction with service quality at Puskesmas Ulee Kareng using the Importance Performance Analysis (IPA) and KANO methods. Data were collected through questionnaires covering 22 service attributes distributed to 100 patients. The IPA results indicate four attributes in Quadrant I that require immediate improvement, including the availability of modern medical equipment, staff readiness to assist patients, efficient admission procedures, and competent medical personnel who build patient trust. The KANO analysis classifies service attributes into Must-be, Attractive, and one-dimensional categories. The integration of IPA-KANO provides strategic priorities to support continuous service quality improvement at Puskesmas Ulee Kareng.